Inovasi Nail Art menggunakan Biji Wijen dengan Teknik Tempel 3D untuk Meningkatkan Kreativitas dalam Desain Kuku - Dani, Ginal Ilmi; Rahmiati, Rahmiati; Astuti, Murni; Dewi, Siska Miga (Lembaga Yasin AlSys, 2025)
This study aims to explore design innovation in Nail Art using sesame seeds through a three-dimensional (3D) applique technique as a creative medium for nail decoration. The method used is experimental with a descriptive quantitative approach. Six designs were developed based on three main themes: flora, fauna, and abstract, utilizing natural sesame seeds, food coloring, and nail polish. The designs were evaluated by seven panelists using four creativity indicators: fluency, flexibility, originality, and elaboration. The results show an average creativity score of 3.73, categorized as “highly creative,” with the highest score found in the fluency indicator at 3.80. These findings demonstrate that sesame seeds can serve as an innovative, aesthetic, and eco-friendly material in nail art. The study concludes that natural material-based innovation, such as the use of sesame seeds, has the potential to enrich Nail Art design development and contribute to enhancing creativity in beauty education. The implications suggest opportunities for utilizing local materials in sustainable and educational aesthetics industries.